Factors Influencing Reduced Scar Tissue Formation Following Unilateral Cleft Lip Plastic Surgeries: a Systematic Literature Review - Marijus Leketas; Bahaa Al Sayegh; Dominykas Latakas; Justina Stucinskaite-Maracinskiene (eJournal of Oral Maxillofacial Research, 2025)
Objectives: Reduction of postoperative scarring after unilateral cleft lip cheiloplasty is a pertinent topic. Smaller scar formation results not only in a better lip function, but also - aesthetics. This systematic review aims to identify various supplementary treatment options which influence favourable scarring outcome after cheiloplasty.